The study of the attributes influencing the decision to live in high-rise condominiums the case of Makati City, Metro Manila, Philippines - Posadas, Marianne Daisy B. (School Urban and Regional Planning, University of the Philippines Diliman, 2023)
Increased preference to live in urban centers has sustained the demand for residential spaces and prompted the proliferation of high-rise residential condominiums especially in key cities in Metro Manila. This trend has notably changed the housing and living set-up of Filipinos. However, the matter of residential planning in urban areas based on preferences of its dwellers has not been widely examined. In addition, local studies on condominiums with an urban planning perspective are limited.